Entrepreneurship education for talent training. An educational experience in high school - Capobianco, Rosaria (Formazione & insegnamento, 2019)
The present contribution, starting from the distinction between enterprise education and entrepreneurship education, focuses on the various aspects of entrepreneurial competence. In particular, the essay presents the structure and the results of the experimentation of a Learning Unit on entrepreneurial competence and enterprise education, realized in a Economic-based Technical Institute of Caserta (Course AFM, Administration, Finance and Marketing) of Caserta, which gave young students the opportunity to express their entrepreneurial talent. The simple experimentation has allowed to understand how the entrepreneurship education is fundamental for the future of the new generations and how there is need of a new formative paradigm.